Experimental investigation and optimization of RMDTM welding parameters for ASTM A387 grade 11 steel. Issue 13 (3rd October 2021) - Bandhu, Din; Kumari, Soni; Prajapati, Vishalkumar; Saxena, Kuldeep K.; Abhishek, Kumar
ABSTRACT: RMD™ welding has been developed for a variety of steels to regulate the rate of metal transfer effectively during the short-circuiting mode of the GMAW process. To achieve the desired weld quality, distinct process variables must be tuned precisely, which leads to an encouraging field of research known as parametric optimization. In this context, the gas flow rate (GFR), current (A), and voltage (V) were chosen as welding variables, and their effects have been examined for the depth of penetration (DOP) and heat-affected zone (HAZ). The work aims to determine favorable parameter settings besides optimizing the aforementioned variables of RMD TM arc weldments. Hence, the satisfaction function approach has been implemented with the Taguchi method to evaluate the favorable process combination. Furthermore, the aforementioned welding variables were again optimized using NSGA II methodology, and a Pareto-front was also drawn for partially evaluating a set of actions with multi-dimensional outputs. The obtained Pareto optimal (PO) solutions aids in revealing the relationship between the performance characteristics and uncover the functioning of the process in an ideal manner. A confirmatory test was also performed, which validates the obtained optimal settings as 100 A current with 16 V voltage and 21 L/min. gas flow rate.